Is there a link between motor learning and mirror neuron system: TMS study - Pomelova, Ekaterina; Feurra, Matteo; Nikulin, Vadim; Grankina, Alena; Solodkov, Roman; Banjevich, Tamara; Blagovechtchenski, Evgeny (Frontiers in Human Neuroscience, 2025)
BackgroundThe mirror neuron system (MNS) activates during the performance of an action and during the observation of the same action being performed by another. At the motor output level, MNS activation manifests as motor resonance, or a muscle-specific increase in corticospinal excitability during action observation. This study focuses on how and to what extent motor learning alters the initial mirror response and whether the rate of motor learning is associated with pretraining or post-training levels of mirror response. The study involved 23 healthy adults aged 22.7 years on average. The experiment consisted of six sessions. On the first and last days, a transcranial magnetic stimulation session was performed to assess the putative activity of mirror neurons, as reflected in the level of motor-evoked potential facilitation during action observation under various conditions. From the second to the fifth sessions (four sessions), motor learning was performed, as represented in the form of a serial reaction time (SRT) task.ResultsWe observed a statistically significant decrease in reaction time during the process of learning within the SRT task and motor facilitation during action observation, thus reflecting putative mirror neuron activity. We found a significant correlation between the learning speed of the non-dominant hand and mirror neuron activation in the dominant hemisphere during the observation of button presses and pinch gestures.ConclusionThe MNS excitability is not a predictor of motor learning, but motor learning is reflected in the characteristics of the MNS.